How Do Extreme Summer Precipitation Events Over Eastern China Subregions Change?. Issue 5 (24th February 2021) - He, Linqiang; Hao, Xin; Li, Hua; Han, Tingting
Abstract: In this study, observations from the CN05.1 daily data set and K‐means clustering were used to capture spatiotemporal characteristics of extreme precipitation events (EPEs) during summer over eastern China subregions from 1961 to 2018. Five subregions including South China (SC), the Yangtze River Basin (YRB), the HeTao Area (HTA), North China (NC), and Northeast China (NEC) are identified, which is distinct from previous studies. There were significant rates of EPEs transfer from the YRB‐type to SC‐type (18%), HTA‐type to YRB‐type (16%), HTA‐type to NC‐type (22%), and NC‐type to NEC‐type (25%), and the associated processes of synoptic evolution are addressed. Within these types of regional EPEs, intrinsic relationships exist that have not been recorded by previous studies. The intraseasonal evolution of summer EPEs shows a northward migration of the rainbelt influenced by the East Asian summer monsoon system. Moreover, temporal variations of regional EPEs from interannual timescales to long‐term trends are examined. Plain Language Summary: The impact of extreme precipitation events (EPEs) on the populations and economies in affected areas has drawn widespread attention; however, the traditional region partition methods could not capture the natural time and space variations and the possible linkages among subregions. Using K‐means clustering, we identified five types of summer EPEs over eastern China during the period 1961–2018. EPEs were more frequent and continuous in the south of this region. Several significant transformation rates (i.e., from one type of EPE transfer to another) exist in these subregions and associated processes of synoptic evolution are addressed. In addition, we investigated the differences and similarities of temporal variations of these types of regional extreme summer precipitation events from shorter timescales to long‐term trends. Key Points: K‐means clustering revealed five distinct types of extreme precipitation events (EPEs) developed over eastern China between 1961 and 2018 The HeTao Area‐type EPEs is recognized as a new type differs from previous studies Five types of events have multitimescale variations, and there are interconnections among them in synoptic and intraseasonal timescale